Impact of wheat lipids on the functionality of wheat flour - Bahrami, Niloufar (2016)
Lipids are minor constituents of wheat flour, but are functional in bread making. As a result they have been extensively studied, but the published results are conflicting. It was therefore the objective of this study to understand better the impact of wheat lipids on wheat flour functionality and to propose approaches for positive modification of the flours. Initial work established quantitative and qualitative assessment methods for the non-starch lipids occurring in starch based systems. Seven solvent systems were compared for their ability to extract the non- starch lipids at ambient temperature. The choice of solvent system greatly influenced the total extractable amounts of lipid and there were differences in the relative composition. Bligh and Dyer methodology showed good extraction ability based on the total amount of non-starch lipids and there was good representation of the different lipid classes (neutral lipids, glycolipids, phospholipids). As this method was reasonable fast, with high extraction ability and showed low coefficient of variation (typically 16%) it was used in subsequent studies including the assessment of lipids in wheats of different variety and the levels and class of lipids segregating in the different mill fractions. As part of a larger study the impact of agriculture based variation in wheat flour chemistry and quality parameters was tested on high quality wheat varieties. Wheat variety was found as the major factor determining wheat flour properties, but environmental effects and post- harvest processing i.e. milling also had an impact. Correlations were made for the composition, flour quality parameters and the bread quality and results showed that whilst proteins are a major determinant for bread texture, lipids significantly influenced bread volume with non-polar lipids significantly and positively associated with bread volume, while the phospholipids reduced dough resistance and therefore may be associated with a decrease in loaf volume. Despite the acknowledged limitation of the data sets in some aspects, the wheats were tested for their “stability” within and over the growing sites. From these data, suggested wheat varieties worthy of further examination have been made. To see if positive modifications could be induced into wheat flours the technique of cold plasma (0.2-0.4 Wcm-2) was applied. It was shown that measureable free fatty acids and phospholipids significantly reduced after treatment and that there was a shift towards higher molecular weight proteins. Markers of oxidation increased and there was a significant increase in hydrogen peroxide and the formation of secondary oxidation products (n-hexanal). All the changes that occurred in the wheat flour during cold plasma treatment ultimately resulted in stronger dough. This suggests that cold plasma is an effective treatment for modifying functionality and enhancing the oxidative state of wheat flour.